LIGHT - ICON/STAINED GLASS - ILLUMINATION. - CHIRILĂ, IOAN; PAȘCA-TUȘA, STELIAN; POPA-BOTA, IOAN; TRIF, CLAUDIA-COSMINA (Journal for the Study of Religions & Ideologies)
God revealed to man during the history of his salvation in two ways: through word and through image. In other words, the divine message was addressed to the hearing and seeing of man. In the second case, revelation was achieved in a complete form. Man was part of a theophanic act, he was enveloped by the divine light and with the help of his spiritual eyes he was able to see, as much as it was permitted, God who is light. This light was not completely strange to man, even though he could not see it with his physical eyes. The uncreated light that God made even from the first day of creation did not disappear when the great light were put in the sky. It had the purpose to arrange creation and to be the environment within which man could meet God and talk to Him face to face. Even though the fall took man out of sight, God established that from time to time this bright environment should be revealed to man in order to call him back to the life within light. These presentations of the Lord in the light of His glory continued after His incarnation. The mystical experiences of the Fathers of the Church (Saint Symeon the New Theologian or Gregory Palamas) constitute a testimony to this respect. But seeing this divine light is not reserved exclusively to the mystics, but may be experienced, partly, by the faithful nowadays. The present study endeavours to provide contemporary man with the necessary premises to experience the sight of the deifying light by means of religious imagery. Whether we have in view (in a proper sense of the expression) icons painted on wood or walls or stained glass imagery, they all contain, hidden within, the kind of light which, once experienced, illuminates man and fills him with light.